2008
DOI: 10.1111/j.1365-2672.2008.03754.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific phenotypic and genotypic variation in toxic cyanobacterialMicrocystisstrains

Abstract: Aims:  We determined if the intra‐specific genetic diversity of Microcystis aeruginosa correlates with phenotypic characteristics. Methods and Results:  Microcystis aeruginosa isolates from various Japanese waters were characterized using genetic analyses based on the 16S–23S rDNA internal transcribed spacer (ITS) region and DNA‐independent RNA polymerase (rpoC1) gene sequences. In addition, morphological and biochemical properties, and the toxicity of M. aeruginosa strains were determined. We found a correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 44 publications
4
47
0
Order By: Relevance
“…The 16S rRNA phylogenetic analysis confirms the results of the most recent phylogenetic analyses on Leptolyngbya (Casamatta et al, 2005;Yoshida et al, 2008;Bruno et al, 2009). Furthermore, most of the sequences reported in GenBank for strains identified as Leptolyngbya species have not been accompanied by morphological, ultrastructural, biochemical or eco-physiological data (Koma´rek & Anagnostidis, 2005;McGregor, 2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The 16S rRNA phylogenetic analysis confirms the results of the most recent phylogenetic analyses on Leptolyngbya (Casamatta et al, 2005;Yoshida et al, 2008;Bruno et al, 2009). Furthermore, most of the sequences reported in GenBank for strains identified as Leptolyngbya species have not been accompanied by morphological, ultrastructural, biochemical or eco-physiological data (Koma´rek & Anagnostidis, 2005;McGregor, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Similar data have been obtained with M. aeruginosa strains by Yoshida et al (2008) using a polyphasic approach, combining phenotypic and genetic characterization. This approach is effective for defining distinct lineages and discriminating the complexity of intra-specific populations.…”
Section: Discussionsupporting
confidence: 79%
“…At the nucleotide level, 10 differ- (27). We recently reported that M. aeruginosa populations have a high degree of genetic diversity at the intraspecies level (31), and their successional blooms revealed different dynamics during the bloom in Lake Mikata (33). We speculate there are various host-phage systems in the relationships between M. aeruginosa and its phages.…”
mentioning
confidence: 85%
“…Separately, we determined partial CRISPR sequences from eight M. aeruginosa strains isolated from the same pond water sample. The eight strains were identified as M. aeruginosa based on specific PCR targeting partial 16S-23S rRNA gene internal transcribed spacers (55). Two strains had a spacer set identical to that of CT1, another two strains were CT4, and another one strain was CT3.…”
Section: Type I-d Crispr/cas System In M Aeruginosamentioning
confidence: 99%